Preliminary studies of bioactive compounds and color in Mexican read wines from Baja California region. - Mendez-Trujillo, Vianey; Gonzalez Mendoza, Daniel (Revista Colombiana de Investigaciones Agroindustriales, 2021)
The total phenolic compounds, total anthocyanin content and antioxidant properties of ten commercially wines based on different grape cultivar from Baja California, Mexico were analyzed. The results showed that the content of phenolic compounds of Vitis vinifera cv. Petit Verdot and Petit Syrah wines had the most highest values of total phenolic content (1188.26 and 1148.13 mg GAE/L, respectively), with respect the another wines. However, wines elaborated with three different cultivars (Cabernet Sauvignon/Petit Verdot/Merlot), and wine from cultivar Petit Verdot presented the highest total flavonoids content (161.06 mg QE/L and 182.64 mg QE/L, respectively) and total anthocyanin content (286.38 mg ME/L and 2548.56 mg ME/L, respectively). In contrast only wine from three grape cultivars (Cabernet Sauvignon/Petit Verdot/Merlot), and wine from cultivar Gamay, exhibits the highest antioxidant activity among tested wines. Finally, these results suggest that wine elaborated with different cultivars (Cabernet Sauvignon/Petit Verdot/Merlot), is more beneficial to health than others red wines in terms of its higher antioxidant activity, total anthocyanin content and total flavonoid content